Mortality risk factors in pneumonic children with congenital heart disease left to right shunt: A case-control study - Fitrih Rahmawati Sulthoni, - (University of Stockholm, 2023)
Children with Congenital Heart Disease (CHD) left to right shunt is closely related to the incidence of respiratory tract infections, especially pneumonia. In resource-limited settings, the mortality rate in children with left-to-right shunt CHD with pneumonia is tremendous. This study aims to evaluate and investigate mortality risk factors for left-toright shunt CHD children with pneumonia during admission. This study is an analytic observational study with a case-control design. We used medical records from January 2016 – December 2021 at Dr. Soetomo General Hospital. Inclusion criteria included children aged six months – five years, diagnosed with pneumonia, had echocardiography results proving a left-to-right shunt CHD, and the outcome at discharge died and/or recovered. Patients with sepsis and septic shock, incomplete medical records, and down syndrome or cerebral palsy were excluded. A total of 96 pneumonia children with left-toright shunt CHD were included consisting of 48 children who survived and died at discharge. The median age of the children was 6 [IQR 3-12] months. The most common type of CHD was Atrial septal defect (ASD), 44.8%, followed by Ventricular Septal Defect (VSD), 20.8%. Those who died were younger, with a median of 4 [IQR 3 – 11.7] months. In multivariate analysis, defect size, desaturation, first antibiotic replacement, and pulmonary hypertension were the risk factors that affected the mortality in pediatric patients with left-to-right shunt CHD and pneumonia with p-values of 0.011, 0.012, 0.004, and 0.008; OR 8.135, 4.95, 6.13, and 6.45 respectively. Mortality risk factors in children with left-to-right shunt CHD and pneumonia are affected by defect size, desaturation, first antibiotic replacement, and pulmonary hypertension. Monitoring the patient's condition based on these underlying factors in order to prevent respiratory complications and improve the patient's survival rate is needed.